Convergent Loss of the Necroptosis Pathway in Disparate Mammalian Lineages Shapes Viruses Countermeasures - Águeda-Pinto, Ana; Alves, Luís Q.; Neves, Fabiana; McFadden, Grant; Jacobs, Bertram L.; Castro, L. Filipe C.; Rahman, Masmudur M.; Esteves, Pedro J. (Frontiers in Immunology, 2021)
Programmed cell death is a vital process in the life cycle of organisms. Necroptosis, an evolutionary form of programmed necrosis, contributes to the innate immune response by killing pathogen-infected cells. This virus-host interaction pathway is organized around two components: the receptor-interacting protein kinase 3 (RIPK3), which recruits and phosphorylates the mixed lineage kinase-like protein (MLKL), inducing cellular plasma membrane rupture and cell death. Critically, the presence of necroptotic inhibitors in viral genomes validates necroptosis as an important host defense mechanism. Here, we show, counterintuitively, that in different mammalian lineages, central components of necroptosis, such as RIPK3 and MLKL, are deleted or display inactivating mutations. Frameshifts or premature stop codons are observed in all the studied species of cetaceans and leporids. In carnivores' genomes, the MLKL gene is deleted, while in a small number of species from afrotheria and rodentia premature stop codons are observed in RIPK3 and/or MLKL. Interestingly, we also found a strong correlation between the disruption of necroptosis in leporids and cetaceans and the absence of the N-terminal domain of E3-like homologs (responsible for necroptosis inhibition) in their naturally infecting poxviruses. Overall, our study provides the first comprehensive picture of the molecular evolution of necroptosis in mammals. The loss of necroptosis multiple times during mammalian evolution highlights the importance of gene/pathway loss for species adaptation and suggests that necroptosis is not required for normal mammalian development. Moreover, this study highlights a co-evolutionary relationship between poxviruses and their hosts, emphasizing the role of host adaptation in shaping virus evolution.